PARADOXIC LANGUAGE "CEBONG-KAMPRET" IN FACEBOOK AS A MIRROR OF THE POLITICAL LANGUAGE OF INDONESIA - Fabianus Fensi (Bricolage : Jurnal Magister Ilmu Komunikasi, 2019)
ABSTRACTCommunication and language are two phenomena from one reality. Language is a means of expressing ways of communicating, and it reciprocally presupposes with communication. Where there is communication, language presence is demanded. Hence the language exists as a medium of communication. This study analyses the language battles of “Cebong-Kampret” on Facebook groups. Two aspects are investigated in this research: logic and ethics. The logic requires the use of language by rules. Language can be understood within the framework of rationality. Ethics requires language that creating peace rather than encouraging hatred. How is the language contested in the battle of “Cebong Kampret” on Facebook? Facebook is a web-based media technology that has its characteristics, such as easily accessed and reach a wider audience. Everyone can be a creator of meaning. The communication process is synchronous and encourages the user’s instant response. This characteristic carries risks. Facebook, in the political context of “Cebong-Kampret,” is paradoxical. People’s political preferences are influenced by Facebook even though the language ignores the logical-ethical language rules. The fight of language in politics is justified as far as upholding the logic and ethics. Logic language teaches the principles based on standards. Misuse of language logic makes language lose its ethical value in practice. Language ethics teaches the principles of good language, which can create peace.Keywords: Language; Logic and Ethicsl; Social Media; Paradox, PoliticsABSTRAKKomunikasi dan bahasa adalah dua fenomena dari satu kenyataan. Komunikasi menyertakan bahasa. Bahasa sebagai alat mengekspresikan berbagai cara berkomunikasi. Bahasa dan komunikasi saling mengandaikan. Dimana terdapat kegiatan berkomunikasi bahasa dituntut kehadirannya. Bahasa hadir sebagai media ekspresi aktivitas komunikasi. Kajian ini menganalisis pertarungan bahasa kelompok “Cebong” dan “Kampret” di facebook. Dua aspek dianalisis, yaitu logika dan etika berbahasa. Logika berbahasa mensyaratkan penggunaan bahasa menurut kaidah sehingga bisa dimengerti dalam kerangka rasionalitas. Etika mensyaratkan penggunaan bahasa yang menciptakan perdamaian bukan mendorong kebencian. Apa yang terjadi dengan bahasa yang dipertarungkan “Cebong” dan “Kampret” di facebook? Facebook adalah media berbasis teknologi web. Dia memiliki karakteristik sendiri, seperti: Dapat diakses dengan mudah. Menjangkau khalayak lebih luas. Setiap orang bisa menjadi pencipta makna. Proses komunikasi berlangsung sinkronik. Mendorong respon instan penggunanya. Karakteristik ini mengandung risiko. Penggunaan facebook, dalam konteks politik “Cebong” dan “Kampret” bersifat paradoks. Preferensi pilihan politik masyarakat dipengaruhi facebook padahal bahasa yang digunakan mengabaikan aturan berbahasa secara logis-etis. Pertarungan bahasa dalam politik dibenarkan sejauh menjunjung tinggi logika dan etika berbahasa. Logika berbahasa mengajarkan prinsip berbahasa berdasarkan aturan. Penyalahgunaan logika berbahasa membuat bahasa kehilangan nilai etis dalam praktiknya. Etika berbahasa mengajar prinsip pemakaian bahasa yang baik. Bahasa yang baik menciptakan perdamaian.Kata Kunci; Bahasa; Logika dan Etika, Media Sosial, Paradoks, Politik.